[SOLVED] -1*-1=1 ? how to prove


by rock.freak667
Tags: prove, solved
rock.freak667
rock.freak667 is offline
#1
Nov19-07, 04:19 PM
HW Helper
P: 6,213
1. The problem statement, all variables and given/known data
Well as the subject states..how does one prove that -1*-1=1?
I think you have to use proof by contradiction but I dont know what to do after assuming that it is not true.
Phys.Org News Partner Science news on Phys.org
Better thermal-imaging lens from waste sulfur
Hackathon team's GoogolPlex gives Siri extra powers
Bright points in Sun's atmosphere mark patterns deep in its interior
rock.freak667
rock.freak667 is offline
#2
Nov19-07, 05:22 PM
HW Helper
P: 6,213
Ok I think I got it...I was told that I should start by knowing that 0*0=0 and that 1-1=0
such that 0*0=0 => (-1+1)*(-1+1)=(-1*-1)-1-1+1=0
(-1*-1)-1=0
and so -1*-1=1
varygoode
varygoode is offline
#3
Nov19-07, 05:36 PM
P: 45
Well, think about what you know about (-1).

Then, think about what you know about (0).

More specifically, note:

0 = (1 + (-1)) and 0 = ((-1)+1)

AND

0 = 0*0.

You should be able to get the algebraic proof from there.

EDIT: Dang, you got it already. Good job, but don't double post, just edit your original post.


Register to reply

Related Discussions
[SOLVED] Prove Precalculus Mathematics Homework 7
[SOLVED] Prove: Sum of angles > 180 in curved space Calculus & Beyond Homework 4
[SOLVED] Prove that the cuberoot of 2 is irrational Calculus & Beyond Homework 9
[SOLVED] Help me prove this inequality Calculus & Beyond Homework 5
[SOLVED] Prove it Linear & Abstract Algebra 6